The Role of Diction in Shaping Brand Image to Influence Consumer Choice in the Digital Age - Andriadi, Dian; Sofyan (LADU: Journal of Languages and Education, 2024)
Background: While product quality and pricing remain important, the language used in branding and marketing plays a pivotal role in building trust and emotional resonance. Purpose: This study explores the impact of diction as a linguistic strategy in shaping brand image and influencing consumer choice in the digital era. Design and methods: Through a literature review methodology, this research highlights how strategic word choices in branding, product descriptions, and marketing campaigns can create emotional connections and enhance consumer trust. Results: The findings emphasize the importance of integrating linguistic elements into marketing strategies to improve the competitiveness of local products in an increasingly digitalized marketplace.